PROTOTYPE PENGENDALIAN DAYA LISTRIK AC DAN LAMPU DENGAN ANALISIS STANDAR KENYAMANAN RUANGAN BERBASIS ATMEGA 2560 - Dwi Krisna Putra Sudiharta, Made; Dyana Arjana, I Gede; Indra Partha, Cok Gede (Jurnal SPEKTRUM; Vol 5 No 2 (2018): Jurnal SPEKTRUM, 2018)
The use of air conditioners (AC) and lighting that do not suit the needs and excessive results in a lack of comfort and high use of electrical energy. Ultrasonic Sensor of SRF-04 functions to find out the number of people in the room, temperature sensor of DHT 22 functions to calculate the temperature and humidity inside and outside the room, Light Intensity sensor of GY-302 functions to read the level of light intensity in the room and micro controller of Arduino Mega 2560 functions to process all input sensors become the command for operating the AC units and lights. The AC and lighting control system working well and can determine the time and number of AC and light that is needed. Those are based by Indonesian room comfort standards so that it can increase the comfort of the room in terms of cooling systems and room lighting with a temperature of 22oC to 25 oC and light intensity of 300 lux.